Mediocrity and induced reciprocity - Natalia Montinari; Antonio Nicolo; Regine Oexl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
We report evidence from an experiment where a principal chooses an agent out of two to perform a task for a fixed compensation. The principal's payoff depends on the agent's ex-ante ability and on a non-contractible effort that the agent has to exert once employed. We find that a significant share of principals select the mediocre agent (i.e. the one with the lower ex-ante ability). When the principal is allowed to send a message, mediocre agents exert more effort than agents with higher ability, and principals who choose mediocre agents on average have a larger payoff than principals who select agents with higher ability. This difference in effort overcompensates the difference in ability. Mediocre agents reciprocate more than agents who have ex-ante higher ability when the principals are able to make them feeling indebted.
Keywords: C9; 330; reciprocity; communication; incentives; mediocrity